Co-opting the ‘public’ in public health: homelessness and the specious logic of discretionary displacement in a mid-sized US city - Lesley Jo Weaver; Claire W. Herbert; Dylan J. Podrabsky; Mackenzie L. Ní Flainn (Critical Public Health)
In the name of public health protection, individuals and communities perceived to be diseased have long been coercively regulated through surveillance, sequestration, or various forms of criminal punishment. In the U.S., people experiencing homelessness (PEH) have been increasingly targeted by social control measures such as containment, banishment, or arrest, often under the guise of public health protection. This study explores how city employees and service providers we term ‘authorities’ use public health justifications to rationalize displacing PEH encamped on public property. We find that authorities draw on sensationalized ‘disease-model’ logics of health risk that pathologize PEH as vectors of infectious disease and drug-related harms. This approach allows authorities to rationalize their decisions to displace, but it locates responsibility for the social challenge of homelessness on homeless people themselves, without providing any resources to mitigate ostensible public health concerns for either PEH or the larger public. We conclude that displacement decisions appear logical only when authorities use a specious logic that disqualifies PEH from the ‘public’ being protected. By identifying coercive patterns in public health history and connecting them with the regulation of unsheltered homelessness, this analysis reveals an all-too-familiar picture, where those with power take coercive action upon those with less power instead of employing preventative or structural interventions that could meaningfully address homelessness.